2018
DOI: 10.18203/2320-6012.ijrms20180627
|View full text |Cite
|
Sign up to set email alerts
|

Study of prescription pattern of drugs used in the treatment of osteoarthritis in a tertiary care teaching hospital: an observational study

Abstract: Background: Osteoarthritis(OA) is a major cause of chronic pain and lower extremity disability among the elderly due to its predilection for lower extremity joints such as the knee and hip. Although Paracetomol is the initial drug of choice, NSAIDS are also frequently used in the symptomatic relief of osteoarthritis. But still, there is a need for safe and effective alternative treatments which would provide both symptomatic improvement and disease modifying effects in OA. The primary objective was to study th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 13 publications
2
16
0
Order By: Relevance
“…This is comparable to a study by Oliveria et al 14 In our study, numerous kinds of medicines were prescribed, with NSAIDs (75%) being the most typically prescribed, both in monotherapy and combined therapy followed by tramadol (60%) calcium supplements (54%), vitamin D3 (52%), paracetamol (34%), glucosamine and chondroitin sulphate in combination (21%), methyl prednisolone (34%) and also in the pattern of prescribing in osteoarthritis patients, NSAID'S were most commonly prescribed (75%) and aceclofenac was the most frequently prescribed drug (52%). This is comparable to a study by Gupta et al 15 In the study conducted, it was found that combination therapy of NSAIDS, calcium and vitamin D3, glucosamine, chondroitin sulphate was the most regularly prescribed therapy in osteoarthritis accounting for 50%. In the study, it was found that 55% of patients were adherent to OA medications, 64% were performing Physical activities and 62% of patients were adherent to Losing weight.…”
Section: Discussionsupporting
confidence: 88%
“…This is comparable to a study by Oliveria et al 14 In our study, numerous kinds of medicines were prescribed, with NSAIDs (75%) being the most typically prescribed, both in monotherapy and combined therapy followed by tramadol (60%) calcium supplements (54%), vitamin D3 (52%), paracetamol (34%), glucosamine and chondroitin sulphate in combination (21%), methyl prednisolone (34%) and also in the pattern of prescribing in osteoarthritis patients, NSAID'S were most commonly prescribed (75%) and aceclofenac was the most frequently prescribed drug (52%). This is comparable to a study by Gupta et al 15 In the study conducted, it was found that combination therapy of NSAIDS, calcium and vitamin D3, glucosamine, chondroitin sulphate was the most regularly prescribed therapy in osteoarthritis accounting for 50%. In the study, it was found that 55% of patients were adherent to OA medications, 64% were performing Physical activities and 62% of patients were adherent to Losing weight.…”
Section: Discussionsupporting
confidence: 88%
“…In this study, the concomitant therapy (Table 7) used in OA patients shows calcium lactate in 549 number of prescriptions, i.e., 72.42% followed by multivitamin B-complex in 96 number of prescriptions, i.e., 12.66% followed by cholecalciferol and muscle relaxants. From the above explanation, calcium lactate was most commonly used concomitant therapy in our study for improvement of health condition of OA patients Lahamate and Razvi most common concomitant therapy prescribed for OA patients, which have similar finding in accordance with our study [17][18][19].…”
Section: Lahamate and Razvisupporting
confidence: 90%
“…8 The Study conducted pantoprazole was most common drug to be prescribed along with NSAIDs used for osteoarthritis patients followed by next common antiulcer agent was rabeprazole which was in contrast with our study. [9][10][11] The study conducted by Famotidine was the most common prescribed antiulcer agents with NSAIDs, in contrast with our study. 12 Our present study also showed the group of antiulcer agents that where prescribed most commonly along with the NSAIDs where H2 receptor antagonists i.e.…”
Section: Discussionmentioning
confidence: 71%